2016
DOI: 10.1111/jan.13029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of work–family–school role conflicts and role‐related social support on burnout in Registered Nurses: a structural equation modelling approach

Abstract: The findings of this study imply that RRSS significantly directly and indirectly influences burnout among the nurses pursuing an advanced degree. It is necessary for nursing managers to consider implementing family- and school-friendly policies (e.g. flexible work schedules) to help nurses to manage their multiple roles and thereby decrease their burnout rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…There are several theoretical and practical implications of these findings. Firstly, role conflicts was a serious problems among RNs pursuing further nursing degree in mainland China, and is consistent with the previous studies [24] which showing that RNs enrolled in educational programs got into trouble to deal with role conflicts. Females have traditionally been responsible for family affairs in Asian countries, and so when they also adopt a worker or student role this would lead to the potential for conflict among these multiple domains.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…There are several theoretical and practical implications of these findings. Firstly, role conflicts was a serious problems among RNs pursuing further nursing degree in mainland China, and is consistent with the previous studies [24] which showing that RNs enrolled in educational programs got into trouble to deal with role conflicts. Females have traditionally been responsible for family affairs in Asian countries, and so when they also adopt a worker or student role this would lead to the potential for conflict among these multiple domains.…”
Section: Discussionsupporting
confidence: 87%
“…family-work-to-school, family-school-to-work, and work-school-to-family role conflicts. The scale reportedly has good validity, with a reliability coefficient of 0.82 [24]. The original scale was translated in the present study into Chinese by three Korean-Chinese nursing researchers using a forward-and-back-translation method.…”
Section: Role Conflictsmentioning
confidence: 94%
See 1 more Smart Citation
“…Reasons for exclusion: Mixed samples lacking independent data (n = 5); Language (n = 1); Did not use MBI (n = 11); Unrelated to study topic (n = 15) Documents included in the systematic review (n = 19) The highest levels of EE were reported by Leiter (1988), and the lowest levels of PA, by Goong et al (2016). The highest levels of DP were found in the study of US nurse supervisors by Lee and Henderson (1996).…”
Section: Levels Of Burnoutmentioning
confidence: 99%
“…A systematic search of the nursing literature reveals that there has been an increasing interest in workplace stress as well as individual and organizational factors that influence nurses' affective and performance consequences. Specifically, a study conducted with nurses in South Korea documented that work-family-school role conflicts exacerbated burnout (Goong, Xu, & Li, 2016). The findings of another study in Taiwan illustrated that surface acting as well as frequency and duration of interaction reduced nurses' job satisfaction, whereas display rules positively affected their job satisfaction (Yang & Chang, 2008).…”
Section: Introductionmentioning
confidence: 99%